Serum salusin-? and salusin-? levels in patients with psoriasis - Erden, Ilker; Ucak, Haydar; Demir, Betul; Cicek, Demet; Bakar Dertlioglu, Selma; Ozturk, Savas; Aydin, Suleyman (John Libbey Eurotext Ltd, 2015)
[Abstract Not Available]
Keywords: Atherosclerosis